Comparison of platelet hemostasis effects for angiotensin receptor blockers in patients with arterial hypertension and metabolic syndrome - I. N. Medvedev; T. A. Kumova (Российский кардиологический журнал)
The authors compared platelet hemostasis effects for two angiotensin receptor blockers, valsartan and eprosartan, in patients with arterial hypertension (AH) and metabolic syndrome (MS). For 16 weeks, 34 patients received valsartan, and 32 - eprosartan. Plasma and platelet lipid peroxidation products, blood and platelet antioxidant potential, platelet hemostasis parameters were investigated. Data were analyzed using Student t statistics. Valsartan therapy in AH and MS patients reduced peroxidation syndrome and optimized primary hemostasis. To reduce body weight in such patients, valsartan should be combined with non-pharmaceutical methods.